Functional results after orthotopic bladder substitution: A prospective multicentre study comparing four types of neobladder. (February 2014) - Paananen, Ilkka; Ohtonen, Pasi; Perttilä, Ilkka; Jonsson, Olof; Edlund, Christer; Wiklund, Peter; Ljungberg, Börje; Möller-Jensen, Klaus; Jonsson, Eirikur; Månsson, Wiking
Abstract: Objective. The aim of this study was to evaluate enterocystometry, voiding pattern and urine leakage of four types of orthotopic bladder substitute. Material and methods. At eight urological departments, 78 consecutive men were studied: 66 with an ileal neobladder [30 Studer pouches (S), 24 Hautmann pouches (H) and 12 T-pouches (T)] and 12 with a right colonic [Goldwasser type (G)] neobladder. Enterocystometry, determination of residual urine, micturition protocol and 24 h pad weight test were performed 6 and 12 months postoperatively. Results. Colonic neobladders had higher pouch pressure at first desire, normal desire and strong desire than ileal neobladders (except at first and normal desire at 12 months) ( p < 0.02) and contraction was present more often at both 6 and 12 months ( p < 0.01 and p < 0.01). Compliance was good in all types of pouch. Intermittent self-catheterization was more common in H patients at 6 months ( p = 0.033). All patients with colonic neobladders used pads during the day and night. In patients with ileal pouches 32% used pads during the day and 70% during the night at 12 months. Urine leakage was higher in patients with colonic bladders at 6 and 12 months during the day (mean/median of 98/31 ml and 82/16 ml versus 10/0 ml and 4/0 ml, p < 0.001). T-pouches had excellent day-time continence, but nocturnal leakage was high. Conclusions. The Hautmann pouch and the Studer pouch behaved similarly at enterocystometry and clinically, and continence was good in the majority of patients. The low number of patients with the other two types of pouch precludes definitive statements.